Pembuatan Film Animasi sebagai Media Pendidikan Literasi bagi Anak Sekolah Dasar - Pratama, Deni Rahman; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractIn this paper discussed "Making Animated Films as Media for Literacy Education for Elementary School Children". This paper aims to provide literacy education to elementary school children. The purpose of writing describes the making of animated films as a medium for literacy education for elementary school children. Writing this paper is done in 3 stages. Based on data analysis, it was concluded that the stage of making animation was as follows. (1) the pre-production stage is the search and discovery of animation ideas, the making of synopsis and storyboard aims to facilitate the process of producing animated films; (2) the stage of production planning, which is carried out with the process of making a model, giving a background, and an animation process carried out with the Adobe Flash Cs6 application used to create characters, and move them before being made an animated film; (3) post-production stage, which is carried out after the creation of animated characters. The making of animated films through the dubbing process is done by recording sound for narration, as well as recording sounds to fill the voices of each of the main characters and supporting characters. Later the editing process using Adobe Premiere Pro CC 2015 was done so that the video could become a unit commonly referred to as film, this process was carried out by combining the pieces of the video from the production planning stage to the rendering process to become an animated film that useful for providing literacy education to elementary school children.Keyword:Â  animated films, literacy